PENGARUH KESADARAN MEREK, CITRA MEREK, LOYALITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN SIKAP MEREK SEBAGAI VARIABEL INTERVENING PADA ONLINE TRAVEL AGENT TIKET.COM - Apsyari, Firdha; Raharjo, Susilo Toto (Diponegoro Journal of Management, 2018)
This research is motivated by the tight competition of Online Travel Agent business in Indonesia. It impact the brand performance of an Online Travel Agent Tiket.com in the last two years and causes a decrease of 1,6%. This study is aimed at showing the influence of Brand Awareness, Brand Image, and Brand Loyalty to the consumer purchase decision through brand attitudes on Online Travel Agent Tiket.com.The data obtained are taken from 100 respondents who are users of Online Travel Agent Tiket.com and are taken by using purposive sampling. The analysis method used in this study is quantitative method including validity and reliability test, classic assumption test, multiple regression analysis, T test, F test, and coefficient determination using SPSS analysis tool.The result of this study shows that brand awareness, brand image, and brand loyalty have such possitive and significant effect to brand attitude. While brand attitude have such possitive and significant effect to the consumer purchase decision.